Propiedades Fisicoquímicas De Suelos Cultivados Con Asparagus Officinalis En La Región Árida Del Noroeste De México - Rosa A. Vázquez; Luis Manuel Lozano Cota; Lamberto Castro Arce; Ramona Icedo García; Beatriz E. Arias-T; Edgar Omar Rueda-Puente (European Scientific Journal, ESJ, 2016)
In the agriculture of arid zones, the inadequate soil management has generated changes in their quality and sustainability, affecting the structure and physicochemical conditions which reduce crop yields; based on the above, is consider as a vital importance the analyses of soil and plants because they provide information, current and accurate, which can be useful to take decisions in relation to soil fertility and plant nutrition. The inappropriate handling and amount of fertilizers in asparagus in the arid region of the Northwest of Mexico, has caused low yields. The aim of this study consisted to analyze soil in seven of the thirteen sub regions of the agricultural coast of Caborca, Sonora, where the asparagus crop has been planted for more than 10 years. The analyzes performed were: percentage of saturation, pH, electrical conductivity (CE), soil texture Nitrogen (NO3), P, K, Na, Ca, Mg and cation exchange capacity. The results showed high levels of Nitrogen and Potassium in almost all the studied sites; on contrary Phosphorus, Calcium and Magnesium, presented values below of the recommended and Electrical conductivity above 5.5. mmhos/ cm. The integration of this information allows appropriate technical advice, to achieve the balance of nutrients, such as to avoid unnecessary costs in fertilizers that the plant might can not take, in addition to the resulting contamination of soil to leach these products.